Value of the HFA-PEFF and H2FPEF scores in patients with heart failure and preserved ejection fraction caused by cardiac amyloidosis. (3rd October 2022) - Tomasoni, D; Aimo, A; Merlo, M; Nardi, M; Adamo, M; Cani, D; Lombardi, C M; Pancaldi, E; Panichella, G; Porcari, A; Vergaro, G; Sinagra, G; et al.
Abstract: Aims: The HFA-PEFF and H2FPEF scores have been developed to diagnose heart failure with preserved ejection fraction (HFpEF), and hold prognostic value. Their use in patients with HFpEF caused by cardiac amyloidosis (CA) has never been investigated. Methods and results: We evaluated the diagnostic and prognostic value of the HFA-PEFF and H2FPEF scores in 304 patients from 3 cohorts with HFpEF caused by transthyretin (ATTR)-CA (n=160, 53%) or immunoglobulin light-chain (AL)-CA (n=144, 47%). A diagnosis of HFpEF was more likely using the HFA-PEFF score with 2 (1%), 71 (23%), and 231 (76%) patients ranked as having a low (0–1), intermediate (2–4) or high (5–6) probability of HFpEF, respectively. Conversely, 36 (12%), 179 (59%) and 89 (29%) of patients ranked as having a low (0–1), intermediate (2–5) or high (6–9) probability of HFpEF using the H2FPEF score. During a median follow-up of 19 months (interquartile range 8–40), 132 (43%) patients died. The HFA-PEFF score, but not the H2FPEF, predicted a high risk of all-cause death which remained significant after adjustment for age, AL-CA diagnosis, high-sensitivity troponin T, N-terminal pro-B-type natriuretic peptide, and echocardiographic parameters, including left ventricular (LV) global longitudinal strain, LV diastolic function and right ventricular function (hazard ratio 1.51, 95% confidence interval 1.16–1.95, p=0.002 for every 1-point increase in HFA-PEFF). Conclusions: The HFA-PEFF score has a high sensitivity to diagnose HFpEF caused by CA and holds independent prognostic value for all-cause mortality, while the H2FPEF score does not. Funding Acknowledgement: Type of funding sources: None.